Emergent leadership among tenants with psychiatric disabilities living in supported housing. (25th December 2017) - Piat, Myra; Sabetti, Judith; Padgett, Deborah
Abstract: The overall aim of this study was to explore the experiences of people with psychiatric disabilities living as tenants in independent, supported apartments for the first time. Supported housing provides an alternative to structured, custodial housing models, such as foster homes, or board‐and‐care homes, for clients in public mental health systems. This article reports findings on how leadership emerged among tenants after making the transition from custodial to supported housing. Semi‐structured interviews were conducted with tenants ( n  = 24) and included questions on their housing history, current living situation, relationships with staff, participation, and understanding or experience of leadership. Interviews were transcribed verbatim, codes generated, and a thematic analysis conducted using a constructivist approach. The findings revealed an understanding and appreciation of leadership among tenants, who identified six pathways to leadership in their housing as a response to unmet tenant needs. Most tenant leaders emerged outside of formal authority or power structures. Supported housing provides a unique social setting and empowering community where the potential of persons with psychiatric disabilities to assume leadership may be realized and further developed. Mental health professionals working in community housing networks are well placed to harness these face‐to‐face tenant communities, and their natural leaders, as an additional tool in promoting tenant recovery, mutual help, neighbourhood integration, and the broader exercise of citizenship.